Protestantika Jožeta Rajhmana - Vinkler, Jonatan (Edinost in dialog, 2025)
The article uses textual genealogy and the history of ideas to analyse Jože Rajhman's historiography of the Reformation. It demonstrates how Rajhman's historio- graphical approach is deeply ingrained in the historiographical and religious currents and changes that occurred in Europe in the second half of the 20th century, such as ecumenism, the development of inter- and multidisciplinary approaches, historiographical history, the - sis-driven historiography under communist totalitarianism, and methodological advances in historiography. As a contemporary, multidisciplinary historian who integrates theology, philology, ecclesiastical history, and literary history, Rajhman stands out in his academic works on Slovenian Protestantism. His thoughts on Luther and the Reformation are in line with those of post-World War II scholars who created new lines of inquiry in German Catholic historiographical circles (e.g., Lortz, Iserloh, Manns). Thus, Rajhman's writings serve as afoundational corpus for contemporary historiography on Primož Trubar and Slovenian Protestantism in the 16th century.
Keywords: historiografija; historiography; interdisciplinarity; interdisciplinarnost; Protestantism; protestantizem